Low-frequency repetitive transcranial magnetic stimulation for children and adolescents with first-episode and drug-naïve major depressive disorder: A systematic review - Zheng, Wei; Lan, Xian-Jun; Qin, Zhen-Juan; Yang, Xin-Hu; Shi, Zhan-Ming (Frontiers in Psychiatry, 2023)
Objective: This systematic review of randomized controlled trials (RCTs) was conducted to explore the therapeutic effects and safety of active low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) versus sham LF-rTMS in children and adolescent patients with first-episode and drug-naïve (FEDN) major depressive disorder (MDD). Methods: A systematic literature search was performed, and data were extracted by two independent researchers. The coprimary outcomes were study-defined response and remission. Results: A systematic search of the literature yielded 442 references, of which 3 RCTs (130 children and adolescents with FEDN MDD, 50.8% male, and mean age range from 14.5 to 17.5 years) met the inclusion criteria. Among the two RCTs (66.7%, 2/3) examining the effects of LF-rTMS on study-defined response and remission and cognitive function, active LF-rTMS was more efficacious than sham LF-rTMS in terms of study-defined response rate and cognitive function (all P<0.05) but not regarding study-defined remission rate (all P>0.05). No significant group differences were found with regard to adverse reactions. None of the included RCTs reported the dropout rate. Conclusion: These findings preliminarily found that LF-rTMS could benefit children and adolescents with FEDN MDD in a relatively safe manner, although further studies are warranted.